Characterisation of Shiga toxin-producing Escherichia coli O157 strains isolated from humans in Argentina, Australia and New Zealand - Leotta, G. A. (2008)
Fil: Leotta, Gerardo A. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Servicio Fisiopatogenia; Argentina.